2014
DOI: 10.1179/1754762814y.0000000100
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits from cochlear implantation of children with unilateral hearing loss

Abstract: Children with acquired UHL are likely to gain similar positive benefits from cochlear implantation as those recently reported in adults (improved localization and better speech understanding in specific noise conditions). However, implantation of children with prelingual UHL is currently problematic as the impact of UHL may not become apparent until the child enters full-time education, by which time outcomes from cochlear implantation may be sub-optimal due to auditory deprivation. Development of appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 122 publications
0
16
0
2
Order By: Relevance
“…Determining benefit can be difficult because studies have found subjective reports of benefit with conventional hearing aids despite no change in speech perception scores . Questions regarding optimal management of UHL continue to gain importance as interest grows in surgical options such as bone conduction hearing devices and even cochlear implants …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining benefit can be difficult because studies have found subjective reports of benefit with conventional hearing aids despite no change in speech perception scores . Questions regarding optimal management of UHL continue to gain importance as interest grows in surgical options such as bone conduction hearing devices and even cochlear implants …”
Section: Discussionmentioning
confidence: 99%
“…28 Questions regarding optimal management of UHL continue to gain importance as interest grows in surgical options such as bone conduction hearing devices and even cochlear implants. 29,30 The age at which an intervention is applied may also affect outcome. For example, Johnstone et al found that children who received hearing amplification earlier in life were more likely to show bilateral benefit with sound localization; however, children who were fit with hearing aids later in childhood or adolescence were more likely to experience bilateral interference with localization with hearing aids in place.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first systematic review of the literature on cochlear implantation in children with UHL. To date, only two nonsystematic reviews have been published . There are only a few original articles on this topic, and we found that the current best available evidence consists of case series.…”
Section: Discussionmentioning
confidence: 92%
“…To date, only two nonsystematic reviews have been published. 21,22 There are only a few original articles on this topic, and we found that the current best available evidence consists of case series. Heterogeneous findings were reported on speech perception in noise and sound localization by four studies, whereas improvement on QoL and speech and language development were only reported by one study.…”
Section: Discussionmentioning
confidence: 94%
“…Centres in Europe and America have shown that the artificial input of a CI can be integrated in a normal hearing ear and provide binaural hearing benefits while successfully reducing the burden of tinnitus during active CI use [Van de Heyning et al, 2008;Kleinjung et al, 2009;Vermeire and Van de Heyning, 2009;Buechner et al, 2010;Carlyon, 2010;Masgoret et al, 2010;Arndt et al, 2011;Arts et al, 2012;Firszt et al, 2012;Ramos et al, 2012;Gartrell et al, 2014]. Recently, children with UHL have been treated with CI [Hassepass et al, 2013], and the development of appropriate candidacy criteria will be challenging [Boyd, 2014].…”
Section: Discussionmentioning
confidence: 99%